The analogy of grace: Karl Barth's moral theology - McKenny, Gerald P. (Oxford University Press, 2010)
Introduction : an overview of Barth's ethics -- The problem of ethics -- Barth's moral theology and modern ethics -- Dogmatics and ethics -- The divine claim -- Human moral action -- Ethical reflection and instruction